2022
DOI: 10.3847/1538-4357/ac70c5
|View full text |Cite
|
Sign up to set email alerts
|

A Library of Synthetic X-Ray Spectra for Fitting Tidal Disruption Events

Abstract: We present a tabulated version of our slim-disk model for fitting tidal disruption events (TDEs). We create a synthetic X-ray spectral library by ray-tracing stationary general relativistic slim disks and including gravitational redshift, Doppler, and lensing effects self-consistently. We introduce the library to reduce computational expense and increase access for fitting future events. Fitting requires interpolation between the library spectra; the interpolation error in the synthetic flux is generally <1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…At the time of writing, only 3 of the 100+ known TDEs in our new TDE catalog have been successfully analyzed for M • and a • using the techniques in Wen et al (2020Wen et al ( , 2021 and Cao et al (2023): Each of these analyses required a minimum computational time of 10 4 CPU hours. However, new interpolation techniques are now able to closely mirror those prior results at much less computational expense (∼10 CPU hours) (Wen et al 2022b). The large number of TDEs with archival X-ray spectra in our new catalog, as well as the expected growth in discovery rates (∼10 2 -10 3 per year), shows the utility of the new interpolation methods for constraining the distributions of M • and a • for TDEs for the first time.…”
Section: Prioritizing Tdes For Analysismentioning
confidence: 66%
See 3 more Smart Citations
“…At the time of writing, only 3 of the 100+ known TDEs in our new TDE catalog have been successfully analyzed for M • and a • using the techniques in Wen et al (2020Wen et al ( , 2021 and Cao et al (2023): Each of these analyses required a minimum computational time of 10 4 CPU hours. However, new interpolation techniques are now able to closely mirror those prior results at much less computational expense (∼10 CPU hours) (Wen et al 2022b). The large number of TDEs with archival X-ray spectra in our new catalog, as well as the expected growth in discovery rates (∼10 2 -10 3 per year), shows the utility of the new interpolation methods for constraining the distributions of M • and a • for TDEs for the first time.…”
Section: Prioritizing Tdes For Analysismentioning
confidence: 66%
“…From our past work (Wen et al 2022b) and, as shown later in Figure 2, we have learned that this exposure time produces counts in most nearby TDEs that are adequate to constrain M • and a • . 2.…”
Section: Deep Multiepoch Observationsmentioning
confidence: 88%
See 2 more Smart Citations
“…Meanwhile, TDE statistics and the physics in their different regimes of evolution (Figure 1), allow us to address many more questions of broad relevance for extragalactic astrophysics (Section 2.2). These are aided by simulations that have not only allowed to confirm some of the assumptions in the early analytical models but have also allowed to expand the regime of TDE parameter space to include different types of disrupted stars, different stellar orbits including high penetration factors, extreme stellar compression, spinning and non‐spinning SMBHs, single and binary stars, and single and binary SMBHs; some regimes only accessible numerically in very advanced computer simulations (Andalman et al 2022; Bonnerot & Wenbin 2022; Bu et al 2022; Coughlin & Nixon 2022; Cufari et al 2022; Ryu et al 2022b; Wen et al 2022, and references therein) with many new predictions of observable facets of TDEs.…”
Section: Stellar Tidal Disruption Eventsmentioning
confidence: 99%